Digital Leadership, Knowledge Management, and Employee Performance - Holy Arif Wibowo; Indah Sulistyowati; Intan Sari Oktoberia; Zaharuddin Zaharuddin; Irawan R. D. Budianto; Anas Ma’ruf (IJBLE Scientific Publications Community Inc., 2026)
Public-sector digital transformation is often framed as a technological modernization project, yet recurrent difficulties in government digitalization indicate that leadership capability, knowledge governance, and employee engagement are equally decisive. This study examines the effects of digital leadership and knowledge management on employee performance, and tests employee engagement as a mediating mechanism, in a knowledge-intensive public health policy organization in Indonesia. A quantitative cross-sectional census survey was administered to all 56 employees of the Center for Health System Resilience Policy (Pusjak SKK), Ministry of Health of the Republic of Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The measurement model satisfied convergent validity, discriminant validity, and internal consistency criteria, with indicator loadings above 0.70, average variance extracted values above 0.50, and heterotrait-monotrait ratios below 0.90. The structural model explained 65.2% of the variance in employee engagement and 74.4% of the variance in employee performance. Digital leadership and knowledge management had positive and significant direct effects on employee engagement and employee performance. Knowledge management was the strongest antecedent of engagement (β = 0.580, p < 0.001), while employee engagement was the strongest direct predictor of performance (β = 0.475, p < 0.001). The indirect effects of digital leadership and knowledge management on performance through engagement were also significant, indicating partial mediation. The findings suggest that digital capability in public bureaucracies produces performance gains not only through systems and infrastructure, but through engaged employees who are able to convert digital vision and organizational knowledge into policy-relevant work. The study contributes to the integration of Dynamic Capabilities Theory, the Knowledge-Based View, and Job Demands-Resources Theory in explaining performance in knowledge-intensive public organizations in the Global South.